Analisis Pembentukan Portofolio Optimal dengan Menggunakan Model Indeks Tunggal (Studi pada Saham LQ45 Periode 2014-2016) - Taufik Akbar; Wiyuda Hadi Pratama (JMK (Jurnal Manajemen dan Kewirausahaan), 2019)
The purpose of this study is to find out the optimal portfolio stocks formed through the Single Index Model. The research method used in this study is a descriptive research method with a quantitative approach. While the sampling technique uses a purpose sampling technique, with the criteria of stocks entering LQ45 during 2014-2016 respectively. The population contained in this study were 58 shares, and 33 samples were taken. The results of the analysis show that the stocks included in the optimal portfolio category are only 8 shares with the proportion of funds being WSKT 33.18%, PTPP 22.74%, AKRA 7.51%, GGRM 9.57%, TLKM 19.63%, UNVR 4, 65%, PWON 2.42%, and ADRO 0.31%. Based on the optimal stock calculation formed, the portfolio expected return is 0.0364 and portfolio risk is 0.0010.